1999
DOI: 10.1212/wnl.52.9.1839
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lewy body variant of Alzheimer’s disease with pure Alzheimer’s disease

Abstract: Compared with patients with AD alone, those with LBV had a greater frequency of extrapyramidal manifestations, somewhat better recall on a selected memory task at their final evaluation, and a significantly lower frequency of neocortical neurofibrillary tangles at autopsy. There were no differences between the two groups, however, in survival time from entry into the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 32 publications
7
53
1
2
Order By: Relevance
“…2 One possibility is that excess A␤ in AD overloads proteasome capacity, leading to incomplete ubiquitin-dependent degradation of ␣-syn, and accumulation of ␣-syn119, which then can give rise to conventional ␣-syn pathology in some cases. This hypothesis is also supported by the observations that A␤ pathology tends to be relatively more severe than phospho-tau pathology in LBV compared with pure AD 35 and that truncated forms of ␣-syn are proportionally more abundant in LBV compared with DLBD. 16 We have not definitively proven that ␣-syn119 is in an aggregated form in AD, but our findings suggest that this is the case.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…2 One possibility is that excess A␤ in AD overloads proteasome capacity, leading to incomplete ubiquitin-dependent degradation of ␣-syn, and accumulation of ␣-syn119, which then can give rise to conventional ␣-syn pathology in some cases. This hypothesis is also supported by the observations that A␤ pathology tends to be relatively more severe than phospho-tau pathology in LBV compared with pure AD 35 and that truncated forms of ␣-syn are proportionally more abundant in LBV compared with DLBD. 16 We have not definitively proven that ␣-syn119 is in an aggregated form in AD, but our findings suggest that this is the case.…”
Section: Discussionmentioning
confidence: 57%
“…This hypothesis is not inconsistent with the finding that combined conventional Lewy pathology and AD pathology in LBV is not associated with shortened patient survival compared with pure AD. 35 Evidence from cell culture studies suggests that aggregation intermediates (oligomers and protofibrils) of ␣-syn and other proteins implicated in neurodegenerative diseases are neurotoxic whereas ␣-syn monomers are not and mature, fully polymerized fibrils may even have neuroprotective qualities. 2,36 -39 Hence, it is possible that by the time conventional ␣-syn pathology becomes evident and AD turns to LBV, the bulk of damage has already been inflicted by ␣-syn119 oligomers and protofibrils.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with studies 8,22 that indicate that patients with Lewy bodies had higher frequencies of hallucinations, delusions, depression, and confusion. Although other studies 17,18,20 have reported no differences.The strengths of our study included the use of a large, well-characterized sample composed of data collected from AD centers across the United States. Nevertheless, our study had some limitations.…”
mentioning
confidence: 66%
“…5,6 In contrast to this stereotypical pattern, Lewy bodies in AD may also be found concentrated in the amygdala without significant involvement of the brainstem or neocortical regions, 2,3 a distribution that has been called AD with amygdala Lewy bodies. 3,7 These cases with both Lewy body and AD pathology are 8,1418 There is controversy as to whether there are differences in parkinsonian features, 8,14,16,19,20 cognitive deficits, 16,17,[19][20][21] cognitive decline, 8,14 and the presence of visual hallucinations 8,17,18,20,22 between AD with Lewy bodies and AD without Lewy bodies (eTable in the Supplement). These diverse findings may partly reflect the relatively small sample sizes used in some of these studies or the limitations with the clinical or neuropathological data.…”
Section: Main Outcomes and Measures-clinical And Neuropsychiatric Tesmentioning
confidence: 99%
“…39,40 The underlying pathologic substrate of motor signs in AD is not clear. They may 41,42 or may not [43][44][45][46][47] be associated with Lewy bodies. As previously published, 4 in this study motor signs were not significantly related to Lewy bodies.…”
mentioning
confidence: 99%